CHARM PRODUCTION IN DEEP INELASTIC MUON-IRON INTERACTIONS AT 200 GEV/C - Arneodo, M; Aubert, J; Bassompierre, G; Becks, K; Benchouk, C; Best, C; Bohm, E; Debouard, X; Brasse, F; Broll, C; Brown, S; Carr, J; et al. (Springer-Verlag, 1987)
Dimuon and trimuon events have been studied in deep inelastic muon scattering on an iron target at an incident muon energy of 200 GeV. The events are shown to originate mainly from charm production. Comparison of the measured cross sections with data taken at higher muon energies shows that charm production originates predominantly from transverse virtual photons. Within the framework of the photon gluon fusion model this indicates that the parity of the gluon is odd. © 1987 Springer-Verlag.